A novel rapid microwave crystallization of photocatalysts for practical utility in the removal of phenol derivatives. Issue 6 (15th March 2023) - Kubiak, Adam; Wojcieszak, Marta; Fuks, Hubert; Gabała, Elżbieta; Materna, Katarzyna; Sikorski, Marek; Jesionowski, Teofil
Abstract: A new concept of the microwave-assisted process was used for the crystallization of titania nanoparticles. The presented microwave crystallization can be indicated as truly environmentally friendly due to its energy efficiency and very short process time. In addition, it allows one to obtain pure materials without surface defects, which was confirmed by the EPR analysis. The physicochemical properties (such as crystallinity, morphology, and textural properties) of the synthesized TiO2 nanomaterials are strongly dependent on the microwave crystallization temperature. In this work, for the first time, the novel and convenient LED photoreactor was compared directly with the classic high-pressure mercury lamp. Photocatalytic studies showed higher activity in the oxidation of phenol and 4-chlorophenol under UV-LED light, compare to high-pressure Hg-lamp. The reason for improving photo-oxidation performance under LED light is indicated that each of the LEDs has the same parameters, so they can be considered as many single sources of UV radiation occurring throughout the entire cross-section of the reactor. This confirms that microwave-assisted crystallization of TiO2 -photocatalysts and application of LEDs as light sources can be elements of a novel photocatalytic approach toward environmental protection. The presented results show that the simultaneous approach to the development of photocatalysts and novel light is the right route to further develop photocatalysis to enter this process into truly environmental protection. Graphical abstract: Image 1